Air-insufflated high-definition dacryoendoscopy yields significantly better image quality than conventional dacryoendoscopy - Sasaki T (Dove Medical Press, 2017)
Tsugihisa Sasaki,1 Tsutomu Sounou,2 Hideki Tsuji,3 Kazuhisa Sugiyama4 1Sasaki Eye Clinic, Mikuni, Sakai, 2Department of Ophthalmology, Keiju Kanazawa Hospital, 3Department of Ophthalmology, Cancer Institute Hospital, 4Department of Ophthalmology and Visual Science, Kanazawa University Graduate School of Medical Science, Kanazawa, Japan Purpose: To facilitate the analysis of lacrimal conditions, we utilized high-definition dacryoendoscopy (HDD) and undertook observations with a pressure-controlled air-insufflation system. We report the safety and performance of HDD.Methods: In this retrospective, non-randomized clinical trial, 46 patients (14 males and 32 females; age range 39–91 years; mean age ± SD 70.3±12.0 years) who had lacrimal disorders were examined with HDD and conventional dacryoendoscopy (CD). The high-definition dacryoendoscope had 15,000 picture element image fibers and an advanced objective lens. Its outer diameter was 0.9–1.2 mm. Air insufflation was controlled at 0–20 kPa with a digital manometer-based pressure-controlled air-insufflation system to evaluate the quality of the image. The HDD had an air/saline irrigation channel between the outer sheath (outer diameter =1.2 mm) and the metal inner sheath of the endoscope. We used it and the CD in air, saline, and diluted milk saline with and without manual irrigation to quantitatively evaluate the effect of air pressure and saline irrigation on image quality.Results: In vivo, the most significant improvement in image quality was demonstrated with air-insufflated (5–15 kPa) HDD, as compared with saline-irrigated HDD and saline-irrigated CD. No emphysema or damage was noted under observation with HDD. In vitro, no significant difference was demonstrated between air-insufflated HDD and saline-irrigated HDD. In vitro, the image quality of air-insufflated HDD was significantly improved as compared with that of saline-irrigated CD.Conclusion: Pressure-controlled (5–15 kPa) air-insufflated HDD is safe, and yields significantly better image quality than CD and saline-irrigated HDD. Keywords: pressure-controlled air-insufflated, high-definition dacryoendoscopy, saline-irrigated dacryoendoscopy, emphysema